2018
DOI: 10.5664/jcsm.6972
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Positive Airway Pressure Therapy in Gestational Diabetes With Obstructive Sleep Apnea: A Randomized Controlled Trial

Abstract: Registry: ClinicalTrials.gov; Title: Obstructive Sleep Apnea and Gestational Diabetes: Incidence and Effects of Continuous Positive Airway Pressure Treatment on Glucose Metabolism; Identifier: NCT02108197; URL: https://clinicaltrials.gov/ct2/show/NCT02108197.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(85 citation statements)
references
References 51 publications
(56 reference statements)
1
84
0
Order By: Relevance
“…The potential for CPAP treatment to benefit glucose metabolism in women with mild OSA and diet‐controlled gestational diabetes was assessed in a small randomized trial . In all, 18 women were randomized to receive CPAP treatment and 18 women (on a CPAP waiting list) were randomized to standard care, at an average gestational age of 30.3 weeks.…”
Section: Sdb With Adverse Pregnancy Outcomes: Potential Mechanismsmentioning
confidence: 99%
“…The potential for CPAP treatment to benefit glucose metabolism in women with mild OSA and diet‐controlled gestational diabetes was assessed in a small randomized trial . In all, 18 women were randomized to receive CPAP treatment and 18 women (on a CPAP waiting list) were randomized to standard care, at an average gestational age of 30.3 weeks.…”
Section: Sdb With Adverse Pregnancy Outcomes: Potential Mechanismsmentioning
confidence: 99%
“…Small studies indicate that CPAP is safe, can be tolerated in pregnancy, and may improve pregnancy-induced hypertension, pre-eclampsia and GDM [50]. However, the evidence for this is not unequivocal [53], and larger scale randomised controlled trials are needed to fully understand the threshold at which intervention might be helpful.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Pregnancy, and particularly late gestation, has been associated with a relatively high prevalence of altered sleep patterns including restricted sleep duration, fragmented sleep, snoring, and especially OSA [55][56][57][58][59][60][61][62][63][64][65][66][67] . Experimental evidence in murine models has conclusively demonstrated that OSA can induce changes in insulin sensitivity and promote obesogenic behaviours as well as hypertension, i.e., correlates of pre-eclampsia [68][69][70][71][72][73][74] .…”
Section: Obstructive Sleep Apnoea During Pregnancy and Consequences Tmentioning
confidence: 99%